Selected shade tree species improved cocoa yields in low-input agroforestry systems in Ghana - Asitoakor, B.K.; Vaast, Philippe; Raebild, A.; Ravn, H.P.; Eziah, V.Y.; Owusu, K.; Mensah, E.O.; Asare, R. (Elsevier, 2022)
CONTEXT Cocoa agroforestry systems differ in the diversity of shade tree species composition. Though cocoa benefits from shade, there is a lack of species-specific information on shade trees that enhance soil fertility and yield.